Kinetic Studies of Metalloporphyrins Bonding with Nitric Oxide - Zhao, Tianxiang; Zhang, Jianbin; Li, Kaixing; Xu, Qiuxia; Lan, Gongjia (Asian Journal of Chemistry, 2014)
At room temperature, the bonding of metalloporphyrins with nitric oxide was investigated in dichloromethane by conventional fluorescence and UV-visible techniques. Spectral analyses showed that metalloporphyrins can react with nitric oxide in a nitric oxide-saturated solution. The experimental rate follows a pseudo first order reaction for metalloporphyrins. The bonding kinetic rate constant of zinc tetraphenylporphyrin with nitric oxide for 0.01965 min-1 and the half-life of bonding was 35.27 min. The bonding kinetic rate constant of magnesium tetraphenylporphyrin with nitric oxide for 0.02184 min-1 and the half-life of bonding was 31.74 min. The experimental results showed that the coordination of magnesium tetraphenylporphyrin with nitric oxide is easier than Zinc tetraphenylporphyrin with nitric oxide.